Do we need an extra dimension? A pilot study on the use of three‐dimensional anorectal manometry in children with functional constipation. Issue 10 (4th April 2022) - Baaleman, Desiree F.; Vriesman, Mana H.; Benninga, Marc A.; Bali, Neetu; Vaz, Karla H.; Yacob, Desale; Di Lorenzo, Carlo; Lu, Peter L.; Koppen, Ilan J. N.
Abstract: Background: Recently, a new high‐definition (or three‐dimensional "3D") high‐resolution anorectal manometry (3D‐ARM) catheter has been introduced. This catheter allows for a more detailed visualization of the anal canal. However, its clinical utility and tolerability in children with constipation are unknown. Our primary objective was to evaluate the agreement between findings from solid‐state high‐resolution anorectal manometry (HR‐ARM) and 3D‐ARM. Secondary objectives were to investigate if 3D‐ARM has additional value over HR‐ARM and to evaluate patient and provider experience. Methods: Prospective pilot study including children (8–18 years of age) with functional constipation scheduled for anorectal manometry. Children underwent HR‐ARM and 3D‐ARM consecutively. We compared manometry results of both procedures and collected data on patient and provider experience via self‐developed questionnaires. Key Results: Data of ten patients were analyzed (60% female, median age 14.9 years). In the majority of patients, ARMs were performed awake ( n = 8, 80%). In two patients, the recto‐anal inhibitory reflex (RAIR) was visualized during HR‐ARM but not during 3D‐ARM. Anal canal resting pressures were significantly higher during 3D‐ARM compared to HR‐ARM (median 77 mmHg [IQR 59–94] vs. 69 mmHg [IQR 51–91], respectively, p = 0.037). No significant anatomical or muscular abnormalities were visualized during the 3D‐ARM. The majority of children identified the 3D‐ARM as the more unpleasant (5/7 [71%]) and more painful procedure (6/7 [86%]) and therefore preferred the HR‐ARM (4/7 [57%]). Conclusions & Inferences: In our patient sample, 3D‐ARM was associated with more discomfort without providing more useful information and even resulted in an inconsistent visualization of the RAIR. Abstract : Results of this pilot study indicate that the use of 3D‐ARM in children without known anatomical abnormalities is not preferred above HR‐ARM. In patients with intractable constipation, the use of the 3D‐ARM may cause more discomfort without providing more useful information.